(untitled) (Sociologisk Forskning, 2000)
The operation was unsuccessful, but the patient survived. Varying assessments of the last anti-alcohol campaign in the Soviet Union One of the most widely discussed factors behind fluctuations in mortality in Russia and the former Soviet Union is the so-called Gorbachev anti-alcohol campaign, which was launched in 1985. This large-scale natural experiment in alcohol policy has since then produced very mixed reviews, partly described as successful although more often depicted as a failure. The article presents the wide variety of assessments, and discusses the underlying criteria on which these assessments are made. These criteria most often pertain to the campaign’s goals, implementation, effects and the overall judgement is closely linked to the chosen time perspective. The effects include changes in life expectancy, alcohol consumption (registered as well as illicit), mortality, crime, in addition to other political, social and fiscal consequences. The varied assessments also point to a schism between a narrowly focused epidemiological view of the campaign and a more general sociological and normative approach.